Current status and trend of clinical development of orphan drugs in China - Ziling Xiang; Wengao Jiang; Bo Yan; Junhao Jiang; Hang Zheng (Orphanet Journal of Rare Diseases, 2022)
Abstract Background Rare diseases have been increasingly recognized as unmet medical and health needs worldwide; a growing demand for the development of orphan drugs emerges subsequently. Therefore, it is of great interest for both the Chinese regulatory agency and pharmaceutical companies to keep tract on the clinical development of orphan drugs in China. Objective and method This study aims to reveal the current situation and trend of the clinical development of orphan drugs in China, based on the data collected from the Chinese official platform, dating from January 1, 2013 to December 31, 2021. Results A total of 331 clinical trials for orphan drugs were extracted from the platform, covering 31 rare diseases and 124 drugs. Increases were seen in the annual number of clinical trials and drugs being tested, with a sharp increase after 2018. About the disease types of the 331 trials, Parkinson disease (young-onset, early-onset) (86, 26%), hemophilia (70, 21%), homozygote hypercholesterolemia (60, 18%) were the most common. Furthermore, it was also observed that the largest number of clinical trial units for rare disease in east China (90, 41%) and the smallest number located in northwest China (18, 6%) and northeast China (18, 6%). Conclusions The growth trends illustrate the progress in clinical trial and drug development of rare diseases from 2013 to 2021. However, promoting orphan drugs development still is an important issue in China; at the same time, further efforts should be made for meet the unmet needs of disease types and balance the uneven distribution of medical resources for clinical trial on rare diseases.